Group portrait of the 1957 Saint Christopher Church First Holy Communion Class - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the First Holy Communion Class of the Saint Christopher Church, photographed in front of the church in 1957.